From L2 acquisition to L1 restructuring: phonotactics in perception and production - Cabrelli, Jennifer; Cruz, Jason; Escalante Martínez, John; Finestrat, Irene; Luque, Alicia (Frontiers in Language Sciences, 2026)
IntroductionResearch on first-language (L1) perceptual attrition indicates that second-language (L2) learners can acquire syllabic structures that are dispreferred in the L1 and that such acquisition can yield L1 phonotactic restructuring in phonetic and phonological processing and production. In the current study, we examine the production of coda stops in the L1, Brazilian Portuguese, and the adult L2, English, of a bilingual sample of speakers in an L2 immersion environment. Our first objective is to determine how these bilinguals' languages interact across perception and production. Specifically, we address the following questions within and between languages, respectively: (1) to what degree of accuracy do these speakers produce coda stops in the L2, and does L2 perception accuracy predict L2 production accuracy?; (2) to what degree of accuracy do these speakers produce coda stops in the L1, and does L1 perception accuracy predict L1 production patterns?; (3) does L2 production accuracy predict L1 production patterns? Our second objective is to model potentially asymmetric perception and production relationships in the L1 and L2 after extensive L2 exposure while accommodating variable production patterns within and across speakers.MethodsFifteen adult bilinguals completed a syllable concatenation task in both languages in which they concatenated disyllabic forms from monosyllabic nonce-word pairs. Productions were coded for coda stop realization and repair strategies. Production data were analyzed using mixed-effects logistic regression models, and previously published ABX perception data were used to examine perception-production relationships within and across languages.ResultsParticipants reliably produced a syllabic target free from epenthesis in English and did so 66 percent of the time in Portuguese. However, they avoided coda stops in 19% of L2 productions and 46% of L1 productions. In cases of coda avoidance, speakers largely favored epenthesis of the coda stop, followed by palatalization and deletion.DiscussionPerception accuracy did not predict production accuracy in either language. In contrast, second-language production accuracy predicted first-language production patterns. To model the speakers' asymmetric comprehension and production grammars, variable coda repair strategies, and the variable relationship between the grammars over time, we adopt the Bidirectional Phonetics and Phonology framework.